A Localized Home-based Health Care Delivery Model for Refugees in Jordan - Salim Suleiman; Matthew Nance; Daniel W O'Neill (Health for All Nations, 2018)
Inter-professional teams delivering home-based care hold promise as an effective model for vulnerable populations, but examples of good practice are limited. This case study presents the initial evaluation of a contextualized application of home-based medical care initiated from the faith community in Jordan toward Syrian and Iraqi refugees with constrained access to resources.Reflexive responses to human need by local churches became the basis for home-based medical outreach. Heavily dependent on volunteers, these church-based teams were selected and trained to meet specific needs, inter-professional partnerships were created through networking, and electronic medical records were deployed to facilitate communication and follow-up.The program's standards of operation are delineated, and a program description is included that clarifies matters regarding volunteer selection, training, faith inspiration, communication, continuity, inter-professional partnerships, and addresses obstacles to care. Based on subjective collective observations of team members, the advantages of the model in practice are reported along with lessons learned. These include dignity promotion, contextualization of health in the home, relationship development, inter-faith communication, inter-professional partnerships, and networking with local health professionals of other faiths and NGOs. Limitations of the model and potential applications in other contexts conclude the case study.